The Influence of Triangle Dribbling Training and Students' Eight-Ball Dribbling Training - Hikari Faza Rafiki; Martin Sudarmono (Universitas Negeri Semarang, 2026)
Dribbling skills are one of the basic techniques that are important in the game of football because they play a role in possession, passing opponents, and creating attack opportunities. However, effective practice methods are still needed to improve students' dribbling skills. This study aims to determine the effect of triangular pattern dribbling practice on students' dribbling skills, the effect of number eight pattern dribbling practice on students' dribbling skills, and to compare the difference in the influence of the two practice methods in improving dribbling skills in football matches. The research method used was an experiment with a pretest and posttest design. The research subjects were divided into two groups, namely the triangle pattern dribbling practice group and the eight-digit pattern dribbling practice group. Data collection was carried out through Dribbling ability tests before treatment (pretest) and after treatment (posttest). Data were analyzed using descriptive statistics, normality test, homogeneity test, and t test. The results of the study showed that both training methods were able to improve students' dribbling skills . In the triangle pattern dribbling practice group , an average pretest score of 9.37 and a posttest score of 8.86 were obtained. Meanwhile, in the Dribbling training group, eight patterns were obtained with an average pretest score of 9.67 and 9.03 posttest. These results show that triangle pattern dribbling exercises provide better improvement than eight-digit pattern dribbling exercises. Thus, both training methods are effective in improving students ' dribbling skills in football matches.